Evaluation of Propellant/Stimgun Stimulation Works Using Geomechanical Analysis Based on Well Logging Data in an Effort to Increase Production at the EYP-211 YNK Structure Well in the Jambi Field - Eko Yugi Priyatno (Journal of Petroleum and Geothermal Technology, 2023)
The oil production flow rate of the EYP-211 well is relatively small, only 12.75 BOPD. The small fluid flow rate is caused by the small formation permeability which is only 2.1 mD. Currently the EYP-211 well has been stimulated with Propellant/Stimgun, but not all of the formation layers can be carried out by Stimgun work so that it is necessary to evaluate it with Geomechanical analysis to determine the success of the stimulation work by calculating the Poisson's ratio and Young's modulus which will be analyzed based on well-logging data.Based on the results of the brittleness index and fracability index analysis, the EYP-211 well is recommended to be stimulated at a depth of 632.92 m to 635.46 m. Stimgun work on the EYP-211 well resulted in a fracture with an average fracture width of 0.02035 in, a fracture height of 9.81 ft and a fracture length of 481.09 ft. The formation permeability increased from 2.1 mD to 14.07 mD due to fractures produced by the stimulus. The flow rate of oil production in the EYP-211 well increased from 12.75 bopd to 140 bopd due to the increased permeability generated by the fracture.